2019
DOI: 10.1038/s41598-019-44288-y
|View full text |Cite
|
Sign up to set email alerts
|

Land management strategies can increase oil palm plantation use by some terrestrial mammals in Colombia

Abstract: While the conservation role of remaining natural habitats in anthropogenic landscapes is clear, the degree to which agricultural matrices impose limitations to animal use is not well understood, but vital to assess species’ resilience to land use change. Using an occupancy framework, we evaluated how oil palm plantations affect the occurrence and habitat use of terrestrial mammals in the Colombian Llanos. Further, we evaluated the effect of undergrowth vegetation and proximity to forest on habitat use within p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 71 publications
6
25
0
1
Order By: Relevance
“…iii) Is the relative abundance of phyllostomid trophic guilds in disturbed habitats related to the distance to conserved forests? We expected bats, despite their ability to fly, to decrease their abundance in disturbed habitats as the distance to conserved forests increased, which is similar to patterns observed in terrestrial mammals, other bats, and birds (Galindo-González & Sosa 2003;Socolar et al 2019;Pardo et al 2019) . We expected this because most diurnal refuges of bats are in conserved habitats (Cortés-Delgado & Sosa 2014) .…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…iii) Is the relative abundance of phyllostomid trophic guilds in disturbed habitats related to the distance to conserved forests? We expected bats, despite their ability to fly, to decrease their abundance in disturbed habitats as the distance to conserved forests increased, which is similar to patterns observed in terrestrial mammals, other bats, and birds (Galindo-González & Sosa 2003;Socolar et al 2019;Pardo et al 2019) . We expected this because most diurnal refuges of bats are in conserved habitats (Cortés-Delgado & Sosa 2014) .…”
Section: Introductionsupporting
confidence: 70%
“…We found that the distance to conserved forests does not influence the abundance of phyllostomid trophic guilds in disturbed habitats. Other studies show the opposite effect in non-flying mammals, bats, birds, and trees (Galindo-González & Sosa 2003;Cleary et al 2016;Socolar et al 2019;Pardo et al 2019) . The lack of a significant effect of distance to conserved habitats on bat abundance in disturbed habitats may be related to the variation in habitat disturbance type in our study and the ability of phyllostomids to fly large distances either to migrate or forage (Arnone et al 2016;Esbérard et al 2017;Medellin et al 2018) .…”
Section: Distance To Conserved Forestsmentioning
confidence: 89%
“…Our study detected 57% more species of the native medium-sized to large terrestrial mammals compared to a study carried out in the same area by Rodríguez-Bolaños et al (2015). Comparing with other non-protected areas of the Orinoco basin, we obtained 55% more than that reported in others three types of savannas (Castillo-Figueroa et al, 2019), 45% more than the African oil palm plantation, 21% more than forest (Pardo et al 2019), and 13% more than the morichales . This indicates that the gallery forest is important as a biological corridor among the savannas and pastures; the probability of occurrence in these forests is considerably greater than in other types of forest cover.…”
Section: Discussionsupporting
confidence: 47%
“…In contrast, this region harbors a relatively low level of endemism (Rodríguez-Mahecha et al, 2006;Ferrer et al, 2009). Despite the high biodiversity and studies recently conducted of the region's medium and large mammals (Álvarez & López-Arévalo, 2014;Rodríguez-Bolaños et al, 2015;Olarte-González & Balaguera-Reina, 2015;Mosquera-Guerra et al, 2017;Mosquera-Guerra et al, 2018;Trujillo et al, 2018;Castillo-Figueroa et al, 2019;Pardo et al, 2019), the mammals of the Orinoco River basin are among the least known in Colombia (Hernández et al, 1984;Mosquera-Guerra et al, 2018). The cited studies have a low representatioforest fragmentedn contrast to the size of the Orinoquia and its habitat heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that changes in plantation management can affect mammal communities, and habitat structure is an important determinant of mammal community composition in plantations (Wearn et al, 2019). Mammal species richness (rats and carnivores) (Pardo et al, 2018) and abundance (anteater, armadillo, and deer) (Pardo et al, 2019) in oil palm plantations in Columbia was positively correlated with the density and presence of understory vegetation, and smallholdings in Malaysia had a higher abundance of carnivorous mammals compared to large-scale plantations, probably due to a greater habitat complexity that could provide an important habitat for some species (Azhar et al, 2014a). For example, Common Palm Civets prefer to nest in oil palm with dense mats of ferns and many leaves (Nakashima et al, 2013).…”
Section: Introductionmentioning
confidence: 99%